Utilization of Oil Palm Leaf Rib Waste (Elaeis guineensis) as Material for Making Handicrafts in Aek Batu Village - Ilham Hakiki Harahap; Nurlina Ariani; Amin Harahap; Adila Saftri; Rindiani Rindiani (International Journal of Community Service Implementation, 2026)
This community outreach activity was carried out with the aim of helping residents of Aek Batu Village, Torgamba District, South Labuhanbatu Regency, utilize palm oil (Elaeis guineensis) palm frond waste into innovative handicrafts that have sales value. The product from palm oil (Elaeis guineensis) palm frond waste is a handicraft in the form of a Peacock Replica "Bumer". The population in this study was the community in Aek Batu Village, which numbered 40 people. The community in the village still rarely utilizes palm oil frond waste as a potential local wisdom to be utilized into goods with economical selling prices. The use of palm oil fronds as a basic material for making furniture is one solution to reduce plantation waste while creating products with economic value. This study aims to describe the process and potential of palm oil fronds as furniture materials using qualitative descriptive methods. Data were collected through interviews with craftsmen and field observations, and supported by related literature studies. Research results show that oil palm fronds have good strength and flexibility, and are easily processed into various products such as fruit bowls, handicrafts such as "Bumer" peacock replicas, and other household items. However, challenges include a lack of modern processing techniques and limited market access. With the support of training, technology, and promotion, the use of oil palm fronds can be further developed as an environmentally friendly creative industry with the potential to improve community welfare.